Shortcomings in the Current Amyotrophic Lateral Sclerosis Trials and Potential Solutions for Improvement - Katyal, Nakul; Govindarajan, Raghav (Frontiers in Neurology, 2017)
Amyotrophic lateral sclerosis (ALS), is a clinically progressive neurodegenerative syndrome predominantly affecting motor neurons and their associated tracts. Riluzole, and edaravone are the only FDA certified drugs for treating ALS. Over the past two decades, almost all clinical trials aiming to develop a successful therapeutic strategy for this disease have failed. Genetic complexity, inadequate animal models, poor clinical trial design, lack of sensitive biomarkers, and diagnostic delays are some of the potential reasons limiting any significant development in ALS clinical trials. In this review, we have outlined the possible reasons for failure of ALS clinical trials, addressed the factors limiting timely diagnosis, and suggested possible solutions for future considerations for each of the shortcomings.